Security versus bank finance: The importance of a proper enforcement of legal rules - Franco Modigliani; Enrico Perotti (Fondazione Eni Enrico Mattei (FEEM), 1999)
We argue that in an unreliable enforcement regime, transactions tend to become intermediated through institutions or concentrated among agents bound by some form of private enforcement. Provision of funding shifts from risk capital to debt, and from markets to institutions with long term relations. When minority investors' rights are poorly protected, the ability of firms to raise equity capital is impaired, leading to less finance for new risky ventures. More generally, fewer firms will be financed with outside equity, resulting in a low capitalisation relative to GNP and a predominance of internal (unlisted) equity and bank lending over traded securities. We report some supporting evidence on a small set of countries on the correlation between investor protection and development of security markets. We use existing measures of investor protection and corruption, as well as a price measure, the premium on voting stock, which is related to the control premium. In countries where the voting premium is large, corporate financing is dominated by bank lending and equity markets are much smaller. The other indicators are also consistent with our hypothesis, although the sample size is limited.
Keywords: G15; G30; K22; K42; 330; Financial systems; Enforcement of law; Investor protection; Unternehmensfinanzierung; Risikokapital; Kredit; Theorie; Welt